Application of Artificial Neural Networks in Geoinformatics - Saro Lee (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Recently, a need has arisen for prediction techniques that can address a variety of problems by combining methods from the rapidly developing field of machine learning with geoinformation technologies such as GIS, remote sensing, and GPS. As a result, over the last few decades, one particular machine learning technology, known as artificial neural networks, has been successfully applied to a wide range of fields in science and engineering. In addition, the development of computational and spatial technologies has led to the rapid growth of geoinformatics, which specializes in the analysis of spatial information. Thus, recently, artificial neural networks have been applied to geoinformatics and have produced valuable results in the fields of geoscience, environment, natural hazards, natural resources, and engineering. Hence, this Special Issue of the journal Applied Sciences, (3z(BApplication of Artificial Neural Networks in Geoinformatics,(3y (Bwas successfully planned, and we here publish a collection of papers detailing novel contributions that are of relevance to these topics.s
English
Keywords: Spatial Analysis; Artificial Neural Networks; Spatial Database; Global Positioning System (GPS); Remote Sensing; Data mining; Geographic Information System (GIS); Machine Learning; Geoinformatics